Environmental Quality in Accordance with the Licensing Process under the Vision of an Environmental Manager - Emphasis on Automotive Laundering Establishmentst - Bogarim, Everton Pereira de Almeida; Paulus, Landi Aramí Rossato; Cabreira, Rosane Pereira da Silva; Lenis, Jakeline Nataly Roseti; Dias, Ana Paula Abreu; Kunz, Emanueli Reynilda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of the environmental licensing is disciplinary the construction, installation, expansion and operation of establishments and activities users of environmental resources, considered effectively or potentially polluting as well as those capable of causing environmental degradation. In general the process consists of three distinct phases, Preliminary License, Installation License and Operating License, however when necessary may contain a specific step to perform the Environmental Impact Study and Public Hearing. This study aims to assess to what level is the environmental conformity of establishments automotive wash in the city of Dourados-MS with licensing processes obtained. The municipal legislation specific for these establishments is basically restricted action to mitigate impacts caused by oil and chemicals products. The existence of a municipal law, however, has demonstrated the involvement of the same with environmental management practices, as well as the state.